Innovation in KIBS firms: the effects of innovation activities, employees’ level of education, and the sources in the supply chain - Seclen-Luna, Jean Pierre (2024)
There has been a growing interest in the study of knowledge-intensive business services (KIBS) due to the important role that they play in the business processes of their clients. Even though extant literature assumes that KIBS firms are innovators, there is evidence that not all KIBS are equally innovative. Our exploratory research uses data gathered from the National Survey of Innovation in the manufacturing and KIBS industries and uses the LOGIT model on a sample of 311 Peruvian KIBS firms. The effects of innovation activities, employee level of education and the sources in the supply chain on developing innovations are determined. Findings indicate that not all innovation activities positively affect innovation. We found that most of these activities are related to technological innovation, rather than non-technological innovation, and the hiring of graduated personnel favours the development of organisational innovation. However, the interplay with customers, suppliers and competitors gives no benefit concerning the development of innovation.